Knowledge, attitude and self-reported practice of healthcare workers on infection control in a health facility in Akure, Nigeria - Oluwagbemiga, Abiola O.; Akinsete, Shade J.; Ana, Godson R.; Ogunseye, Olusola O. (International Journal of Infection Control, 2021)
Background: Infection control is pivotal in reducing healthcare-associated infections (HAIs), one of the leading causes of morbidity with growing prevalence in sub-Saharan Africa. Objectives: We investigated the knowledge, attitude and self-reported hygiene practices towards hospital infection control among healthcare workers (HCWs) at the State Specialist Hospital, Akure, Nigeria. Methods: This descriptive cross-sectional study involving self-administered, structured questionnaires administered to 137 randomly selected HCWs (19 doctors, 66 nurses and 52 health assistants) was conducted in 2015. Descriptive and inferential statistics were used for data analysis at 5% level of significance. Results: Mean age of HCWs was 39.81 ± 8.69 years. Majority (84.7%) was trained on hand hygiene and was knowledgeable about HAIs (86.9%), modes of transmission (57.7%) and effectiveness of hand hygiene (94.9%). However, about half (48.9%) of the HCWs reported did not adhere to hand hygiene often, because of the distance between a water source and the wards. This study also showed that there are relationships between categories of respondents and their knowledge of routes of HAI transmission (P < 0.01) and practice of hand hygiene after contacts with hospital surfaces (P < 0.01). Conclusions: Hospital and hand hygiene can be improved by ensuring water supply located close to the wards. There is need for the provision of clear guidance on procedures for hospital hygiene and sanitation.